Different Approaches to Issues of Migration and the Stability of Bilateral Relations Between Hungary and Serbia in Light of the Refugee Crisis - Beretka, Katinka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Although Hungary and Serbia assume different status within the European Union, one of their common features is that they are not the final destination of refugees (migrants); however, as transit countries, located in the Balkan route, adopted different migration strategies: Serbia tries to follow pro-migrant policy, or at least suggestions of Brussels, still Hungary expressly objects to any EU measures that beneficially look at the migration process. The goal of this paper is to present the most relevant provisions of legal regulations of Serbia and Hungary regarding migration-management, including 1) conceptualization of the term "migrant" as special category of foreigners, through analysis of rules of border control, process of asylum and temporary protection, and rights of foreigners in general, and 2) legal circumstances of criminalization of migrants and pro-migrant work in legal acts of the both countries. Besides the comparison of different legal approaches of Hungary and Serbia to accompaniments of the refugee crisis in the Western Balkan route, some of the contrasting political declarations are going to be critically demonstrated, in light of the stability of bilateral relations.